1996
DOI: 10.1089/jop.1996.12.471
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Intraocular Pressure Lowering Effect of Timolol Preparations in Rabbit Eyes

Abstract: Two timolol preparations, a gel and an eyedrop with a thickening agent, and one commercial eyedrop without a thickening agent, were studied in rabbits. After topical administration of these three preparations in rabbits, aqueous humor was withdrawn and the proteins removed from the samples by precipitation with acetonitrile. Timolol concentrations were determined directly by an HPLC method. The HPLC mobile phase was composed of methanol and 5 mM d-camphorsulfonic acid (in 1% acetic acid) with a ratio of 49:51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…particularly in patients with comorbid conditions (i.e.. coronary heart disease, asthma). The gel preparation of timolol, with a thickening agent, has a longer duration and a higher ocular bioavailability, 35,3 which corresponds with our results. Carteolol is metabolized by the cytochrome P450 enzyme CYP2D6, which has a drug-metabolizing activity that is polymorphologically distributed in the popula-tion with less than 1% of Japanese individuals lacking normal activity, as opposed to 8% of European Americarns anld 2% to 4% of African Americans classified as poor metabolizer phenotypes.37'38 The genetically determined or pharmacologically induced poor metabolizer by CYP2D6 modulators is possibly susceptible to the systemic adverse effects of topical timolol or carteolol.5223940 Ocular instillation of a carteololophthalmic solution is recommended instead of nasal instillation to avoid systemic adverse effects, even in elderly patients, because ocular instillation can be a more effective and safer route in controlling IOP than nasal instillation.…”
Section: Pharmacokinetics and Pharmacodynamicssupporting
confidence: 89%
“…particularly in patients with comorbid conditions (i.e.. coronary heart disease, asthma). The gel preparation of timolol, with a thickening agent, has a longer duration and a higher ocular bioavailability, 35,3 which corresponds with our results. Carteolol is metabolized by the cytochrome P450 enzyme CYP2D6, which has a drug-metabolizing activity that is polymorphologically distributed in the popula-tion with less than 1% of Japanese individuals lacking normal activity, as opposed to 8% of European Americarns anld 2% to 4% of African Americans classified as poor metabolizer phenotypes.37'38 The genetically determined or pharmacologically induced poor metabolizer by CYP2D6 modulators is possibly susceptible to the systemic adverse effects of topical timolol or carteolol.5223940 Ocular instillation of a carteololophthalmic solution is recommended instead of nasal instillation to avoid systemic adverse effects, even in elderly patients, because ocular instillation can be a more effective and safer route in controlling IOP than nasal instillation.…”
Section: Pharmacokinetics and Pharmacodynamicssupporting
confidence: 89%
“…As a b-blocker, timolol may reduce blood pressure (Chiang et al 1996). There are con¯icting reports on the effects of b-adrenergic blockers on arterial blood pressure after topical application to the eye (Tagawa et al 1995;Tamaki et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of methods to prolong the residence time of b-adrenergic blockers on the cornea is therefore of interest. Solutions of b-blockers are often made viscous by the addition of high molecular weight agents, such as water-soluble polymers of synthetic, semi-synthetic or natural origin (Chiang et al 1996). We suggest the use of tamarind seed polysaccharide (TS-P) (Int.…”
mentioning
confidence: 99%
“…In this study, the observed decrease in IOP is, while statistically highly significant, modest, but similar to that reported by other using normotensive rabbits. [30][31][32] In this proof of principle study, we did not intend to determine the amount of microbeads required to achieve, for example, a reduction of IOP by 5 mmHg since the pharmacokinetics of timolol differ between humans and rabbits. Indeed, previous studies have demonstrated that timolol is less effective in rabbits than humans, [33][34][35][36][37] suggesting that the use of timolol spheres may have a more marked effect in humans, and particularly in eyes with elevated IOP.…”
Section: Discussionmentioning
confidence: 99%